Larvicidal Activity of Silver Nanoparticles Synthesized Using Extracts of Ambrosia arborescens (Asteraceae) to Control Aedes aegypti L. (Diptera: Culicidae) - Bianca Morejón; Fernanda Pilaquinga; Flavia Domenech; Danny Ganchala; Alexis Debut; Marco Neira (Journal of Nanotechnology)
The mosquito species Aedes aegypti is the primary vector of dengue, chikungunya, and Zika infections worldwide. Since effective vaccines or drugs are not available for the prevention and/or treatment of these pathologies, vector control has been adopted as the main approach to reduce their transmission. To control Aedes populations, the most commonly used tool is the application of chemical insecticides and, despite their effectiveness, indiscriminate use of these chemicals has led to high operational costs, appearance of resistant populations, and adverse nontarget effects. Plant-derived insecticides may be an eco-friendly, cost-effective, and safe biocontrol alternative. The present study was carried out to evaluate the larvicidal activity of leaf extracts of Ambrosia arborescens and green-synthesized silver nanoparticles (AgNPs) using aqueous extracts obtained from this plant against third instar larvae of Ae. aegypti. To test this, larvae were exposed for 24 h to the aqueous plant extract at 1500, 3000, 4500, and 6000 ppm and the plant-synthesized AgNPs at 0.2, 0.3, 0.4, and 0.5 ppm. In laboratory assays, AgNPs were more toxic (LC50 = 0.28 ppm; LC90 = 0.43 ppm) than the plant extract (LC50 = 1844.61 ppm; LC90 = 6043.95 ppm). These results suggest that A. arborescens aqueous extract and green-synthesized silver nanoparticles produced from those extracts have the potential to be developed into suitable alternative tools useful for the control of Ae. aegypti populations.